Effects of Three Widely Used Antibiotics and Their Mixture on the Haemocytes of the Clam Ruditapes philippinarum - Nicolussi, Greta; Fabrello, Jacopo; Asnicar, Davide; Ciscato, Maria; Matozzo, Valerio; Marin, Maria Gabriella (Frontiers in Environmental Science, 2022)
Although the presence of pharmaceutical and personal care products in aquatic ecosystems is well documented, little information is available about their sublethal effects, on aquatic invertebrates. From an ecotoxicological point of view, the use of in vitro approaches has been recommended as a tool to assess adverse effects and to understand the mechanisms of action of chemicals at the cellular level. In the present in vitro study, the effects of Amoxicillin (AMX), Trimethoprim (TMP) and Ciprofloxacin (CIP) (1 µg/L) were tested alone and – for the first time – as a mixture (MIX) on haemocytes of the clam Ruditapes philippinarum. After the exposure, a battery of cellular parameters was evaluated, such as haemocyte viability, lysosomal membrane stability, superoxide anion production, acid phosphatase activity, the frequency of micronuclei and chromosomal aberrations. The results demonstrated that AMX, TMP, CIP and MIX affected lysosomal membrane stability, as well as superoxide anion and acid phosphatase production, and promoted chromosomal aberrations. This study highlighted that Manila clam haemocytes are a sensitive cell model to assess the effects of exposure to pharmaceutical products on non-target species. Our study demonstrated that the effects of pharmaceutical mixtures on marine species should be experimentally evaluated because they are not predictable from single exposure as the compounds can interact in different ways on the various biological endpoint considered.